Excited states in hydrogenated single-layer MoS2. (26th November 2020) - Din, Naseem Ud; Turkowski, Volodymyr; Rahman, Talat S
Abstract: Our calculations of the excitation spectrum of single-layer MoS2 at several hydrogen coverages, using a density-matrix based time-dependent density-functional theory (TDDFT) show that the fully hydrogenated system is metallic, while at lower coverages the spectrum consists of spin-polarized partially filled localized mid-gap states. The calculated absorption spectrum of the system reveals standard excitonic peaks corresponding to the bound valence-band hole and conduction-band electron, as well as excitonic peaks that involve the mid-gap states. Binding energies of the excitons of the hydrogenated system are found to be relatively large (few tens of meV), making their experimental detection facile and suggesting hydrogenation as a knob for tuning the optical properties of single-layer MoS2 . Importantly, we find hydrogenation to suppress visible light photoluminescence, in agreement with experimental observations. In contrast, both Li and Na atoms transform the system into an n-doped non-magnetic semiconductor that does not allow excitonic states.